PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN UNSUR INTRINSIK CERITA RAKYAT RIAU SISWA SD - Muthia Raudha; Zufriady; Otang Kurniaman (STKIP Subang, 2026)
This study aims to determine the effect of the Team Games Tournament (TGT) type cooperative learning model on the ability to understand the intrinsic elements of Riau folklore of fourth-grade students at SD Angkasa, Pekanbaru. This study is a quantitative study with the Pre-Experiment method using the One Group Pretest-Posttest Design. The research subjects were 17 students in class IVB. Data collection techniques used were tests, observation sheets, and documentation. The results showed that the average pretest score of students was 79.7 and increased to 95.3 in the posttest. Based on the results of the Paired Samples T-Test, the Sig. (2-tailed) value was 0.001 <0.05 so that H₀ was rejected and Hₐ was accepted. This shows that there is an effect of the TGT type cooperative learning model on the ability to understand the intrinsic elements of Riau folklore of elementary school students. The N-Gain test result of 0.783 is in the high category. Based on the research results, it can be concluded that the cooperative learning model of the Team Games Tournament (TGT) type has an effect on improving the ability to understand the intrinsic elements of Riau folk tales of fourth-grade students at Angkasa Elementary School, Pekanbaru.